The Columbia history of Jews and Judaism in America - Raphael, Marc Lee (Columbia University Press, 2008)
This collection focuses on a variety of important themes in the American Jewish and Judaic experience. It opens with essays on early Jewish settlers (1654-1820), the expansion of Jewish life in America (1820-1901), the great wave of eastern European Jewish immigrants (1880-1924), the character of American Judaism between the two world wars, American Jewish life from the end of World War II to the Six-Day War, and the growth of Jews' influence and affluence. The second half of the volume includes essays on Orthodox Jews, the history of Jewish education in America, the rise of Jewish soc.